2022
DOI: 10.3390/insects13020159
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and Intrasexual Variation in Cuticular Hydrocarbons in Trichrysis cyanea (Linnaeus, 1758) (Hymenoptera: Chrysididae)

Abstract: Cuckoo wasps (Chrysididae, Hymenoptera) are known for their parasitoid or cleptoparasitic life histories. Indeed, the biology of only a few species has been studied in detail and often only little more is known than the host species. By mimicking their hosts’ cuticular hydrocarbon (CHC) profiles, species that parasitize single (or a few closely related) host species manage to deceive their hosts. However, the variability of the CHC profile in generalist cuckoo-wasp species is still unknown. Here, we used gas c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…For compounds B and C, GC–MS data in combination with NMR data were used for identification. The hydrocarbons D and VI were identified by their mass spectra, and the positions of double bonds in compound D were determined by DMDS derivatization (Carlson et al 1989 ; Fröhlich et al 2022 ). The remaining minor compounds (I–V) were tentatively identified by GC–MS data only.…”
Section: Methodsmentioning
confidence: 99%
“…For compounds B and C, GC–MS data in combination with NMR data were used for identification. The hydrocarbons D and VI were identified by their mass spectra, and the positions of double bonds in compound D were determined by DMDS derivatization (Carlson et al 1989 ; Fröhlich et al 2022 ). The remaining minor compounds (I–V) were tentatively identified by GC–MS data only.…”
Section: Methodsmentioning
confidence: 99%
“…Within single populations of non-eusocial hymenopteran species, two co-occurring female CHC phenotypes have been found for Euglossa dilemma (Saleh et al 2021 ), Odynerus spinipes (Wurdack et al 2015 ; Moris et al 2021 ), and Philanthus triangulum (Strohm et al 2008a , 2010 ), while female Trichrysis cyanea have recently been reported to exhibit three different female CHC profiles. However, for the latter species it is as yet unclear whether the observed polymorphism is consistent or simply reflects the females’ reproductive state (Fröhlich et al 2022 ). Despite the observed female CHC polymorphisms, males seemed to exhibit only a single CHC phenotype within a given population in three of these species (Wurdack et al 2015 ; Moris et al 2021 ; Saleh et al 2021 ; Fröhlich et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, for the latter species it is as yet unclear whether the observed polymorphism is consistent or simply reflects the females’ reproductive state (Fröhlich et al 2022 ). Despite the observed female CHC polymorphisms, males seemed to exhibit only a single CHC phenotype within a given population in three of these species (Wurdack et al 2015 ; Moris et al 2021 ; Saleh et al 2021 ; Fröhlich et al 2022 ). Male P. triangulum , however, showed a CHC dimorphism that was similar to that observed for females, but less pronounced (Kroiss et al 2006 ; Strohm et al 2008b ; Strohm, pers.…”
Section: Introductionmentioning
confidence: 99%